Evaluación del efecto de quitosano en la germinación y crecimiento de plántulas de lechuga (Lactuca sativa L.) variedad crespa verde, como bio-estimulante, en el cantón Ibarra – provincia de Imbabura - Hurtado Bastidas, Madelaine Elizabeth (2023)
The uncontrolled application of growth stimulants in agriculture is a problem of absolute relevance, due to the high chemical toxicity of these substances, resulting in health effects and contamination of ecosystems. The objective of this study was to evaluate the effect of chitosan as a biostimulant in plant growth, determining its influence on lettuce seed germination and vegetative response of lettuce seedlings under nursery conditions. Lettuce seeds were subjected to four concentrations of chitosan (0, 1000, 2000 and 3000 mg/l) for an imbibition time of 10 minutes. After 7 days, the germination percentage was determined in the laboratory phase. The best concentration was found to be the T2 treatment (1000 mg/l of chitosan), resulting in a 93% germination rate\; this dose was used in the field phase. To determine the ideal frequency of application, three treatments were evaluated (T1: no application of chitosan, T2: one application of chitosan at 10 DDS (days after planting) and T3: two applications of chitosan at 10 and 20 DDS), after 30 days it was determined that the percentage of emergence was 90. The best results were obtained with T3 in seedling height (11.059 cm), fresh and dry leaf biomass (0.9416 and 0.065 grams), and fresh and dry root biomass (0.203 and 0.016 grams). The T2 concentration (1000 mg/l) in the laboratory phase is ideal for the germination of lettuce green crespa variety\; the T3 frequency (two immersions) in the field phase positively influences the growth of lettuce seedlings.